2013
DOI: 10.1016/j.jtcvs.2012.09.102
|View full text |Cite
|
Sign up to set email alerts
|

Surgical reconstruction of peripheral pulmonary artery stenosis in Williams and Alagille syndromes

Abstract: The data have demonstrate that this comprehensive surgical approach to the treatment of peripheral pulmonary artery stenosis was associated with low early and no late mortality. Surgical reconstruction of the peripheral pulmonary artery stenosis resulted in a significant decrease in right ventricular pressure. We hypothesize that this reduction in right ventricular pressures will confer a long-term survival advantage for this cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 23 publications
0
48
0
1
Order By: Relevance
“…Monge and colleagues [9] from Stanford University reported similar successful outcomes in 16 patients with Williams and Alagille syndromes. Our series did not include any patients with Alagille syndrome, while the Stanford series did not include any patients with arterial tortuosity syndrome.…”
Section: Commentmentioning
confidence: 85%
See 1 more Smart Citation
“…Monge and colleagues [9] from Stanford University reported similar successful outcomes in 16 patients with Williams and Alagille syndromes. Our series did not include any patients with Alagille syndrome, while the Stanford series did not include any patients with arterial tortuosity syndrome.…”
Section: Commentmentioning
confidence: 85%
“…It is important to mention that only 58% of patients in this series had interventions on the lobar or segmental PA (ie, peripheral PA), while the remaining 42% of the patients received only central PA interventions. Unfortunately, most of the published studies for transcatheter therapy for PAS combine the data for central and peripheral PA interventions as 1 group [9][10][11][12][13][14][15][16]. We believe that the use of a classification system to stratify the data based on the level of intervention performed is essential to enable objective comparison of data from various groups and different interventions.…”
Section: Commentmentioning
confidence: 99%
“…Scheiber et al 2 reported in an echocardiographic study that SVAS progressed with age, in spite of occasional spontaneous improvement; while De Rubens Figueroa et al 3 noted that pulmonary artery branch stenosis tended to improve spontaneously, and Monge et al 28 observed the same phenomenon, especially in those with mild to moderate other than those with severe peripheral pulmonary artery stenosis. In contrast to SVAS, pulmonary artery stenosis 17,20,21 in this population often regressed or resolved with time.…”
Section: Adverse Cardiac Eventsmentioning
confidence: 97%
“…Del Pasqua et al 26 proposed that the major surgical or interventional indication for pulmonary stenosis in WS patients was a mean pressure gradient of >45 mmHg. Clinical studies by different surgical teams, including Stamm et al 27 , Monge et al 28 and Geggel et al 29 that the treatment of choice for pulmonary stenosis depended on the site of the lesion and the late results were fine (Fig. 1).…”
Section: Pulmonary Stenosismentioning
confidence: 99%
“…Данная патология успешно корректируется хирургическим путем [32] в случае поражения прокси-мального отдела ЛА, однако в других случаях одним из эффективных вариантов является эндоваскулярная кор-рекция при помощи стентирования [33]. Первый в мире стент Palmaz был разработан фирмой Johnson & Johnson Interventional Systems (США) в 1987 г. для лечения ВПС, в том числе и при обструктивной патологии ЛА.…”
Section: стеноз легочной артерииunclassified